Introduction to thermoacoustic Stirling engines: First steps and praxis - Iniesta Carmen (EDP Sciences, 2021)
The work focuses on the theoretical study and design of Thermoacoustic Stirling-Like Cycle Engines. One of the main goals of this study is to describe the application of a methodology for energy analysis and optimization of thermoacoustic devices. This new approach avoids complicated mathematical treatments, facilitates access to this fascinating technology for all audiences. The presented methodology is based on the distribution of the active and reactive acoustic power flow according to the passive acoustic circuit. In addition, this methodology allows optimizing the device by comparing different acoustic circuits. This method is evaluated at a theoretical level with the models and simulations developed, for each of the case studies described. Besides, this publication shows the praxis from the first steps, so the reader is guided in the design and manufacture of a compact Stirling thermoacoustic energy recovery engine, operating in laboratory conditions. The resulting demonstrator is itself an academic tool for knowledge transfer.